''Crew of Strathcona, July 1921'' (1921)
''Strathcona'' crew members standing in the vessel. This collection includes 23 hand-coloured and 36 black and white lantern slides showing Dr. Grenfell's work in St. Anthony and Conche in Newfoundland, Battle Harbour and Indian Harbour in Labrador as well as Harrington Harbour in Quebec. Neither photographer nor owner of the slides is known. Many are numbered sequentially and were probably used as part of a slideshow for Grenfell Mission fundraising.